2020
DOI: 10.1002/pon.5360
|View full text |Cite
|
Sign up to set email alerts
|

Association between early informed diagnosis and survival time in patients with lung cancer

Abstract: ObjectiveAs a malignant tumor with high mortality, lung cancer (LC) often causes great trauma to patients, and a series of negative emotions and a heavy psychological burden accompanies poor prognosis. Whether or not to inform the patients of their condition has always been a controversial topic in the medical community. This retrospective cohort study investigated the association between early informed diagnosis and survival time in patients with LC.MethodsA total of 29 825 patients with LC were enrolled betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 33 publications
2
12
0
Order By: Relevance
“…On the contrary, without knowing their cancer condition results in an uncompleted understanding of their diagnosis, which would hurt the trust relationship between patients and physicians [22]. Depending on a study of a total of 127 cancer patients and their caregivers, no signi cant difference was found before and after disclosing the cancer diagnosis to patients, while the quality of life could be improved with psychological care intervention [23].We have found that knowing their cancer status would carry a better survival rate in patients with lung cancer, while there were few studies about this issue in breast cancer patients [24].…”
Section: Introductionmentioning
confidence: 91%
“…On the contrary, without knowing their cancer condition results in an uncompleted understanding of their diagnosis, which would hurt the trust relationship between patients and physicians [22]. Depending on a study of a total of 127 cancer patients and their caregivers, no signi cant difference was found before and after disclosing the cancer diagnosis to patients, while the quality of life could be improved with psychological care intervention [23].We have found that knowing their cancer status would carry a better survival rate in patients with lung cancer, while there were few studies about this issue in breast cancer patients [24].…”
Section: Introductionmentioning
confidence: 91%
“…Patients' actual awareness of diagnosis and prognosis was measured in 14 studies. 19,31,32,34,35,39,[43][44][45][46][47][48][49][50]…”
Section: Patients' Actual Awarenessmentioning
confidence: 99%
“…A higher patient's score indicates stronger loneliness. DT is used to reflect the average pain experienced by the patient in the last week, with 1-3 points for mild pain, 4-6 points for moderate pain, 7-9 points for severe pain and 10 points for extreme pain [11,12] .…”
Section: Comparison Of Poms-sf University Of California Los Angeles L...mentioning
confidence: 99%